Managing the open calcaneal fracture: A systematic review. Issue 6 (December 2019) - Spierings, Kimberley E.; Min, Minoesch; Nooijen, Lynn E.; Swords, Michael P.; Schepers, Tim
Highlights: Open calcaneal fractures are associated with high rates of complication. This review includes 18 articles with 616 open calcaneal fractures in 598 patients. The complication rate was 21% and the mean AOFAS score was 73.7. A treatment algorithm is provided. There is a need for a prospective (inter)national database. Abstract: Introduction: Open fractures of the calcaneus are rare. They are mostly caused by high-energy trauma. There are several treatment options for calcaneal fractures. However, treatment of open calcaneal fractures might need a different approach, as open calcaneal fractures are associated with high rates of complications. The purpose of this study was to provide a literature overview on the management of open calcaneal fractures, and deduct a more standardized treatment algorithm. Material and methods: A literature review was conducted in the databases of PubMed, EMBASE and the Cochrane Library for articles describing the management of open calcaneal fractures. Excluded were studies with less than 10 patients, studies describing combat injuries and reviews. Only articles published from 1998 to 2017 were included and there were no language restrictions. Results: A total of 18 articles were included with 616 open calcaneal fractures in 598 patients. Most wounds were Gustilo grade III and most fractures were Sanders type III. Definitive surgery was performed after a mean of 9.8 days and in most cases in the form of ORIF via ELA. The complication rate was 21% and the mean AOFAS score was 73.7 points. Conclusion: The complication rates of open calcaneal fractures are high and increase with the severity of the wound. A treatment algorithm is suggested. However, to produce a more evidence-based protocol and achieve consensus for treatment, additional research should be done, preferably in the form of a prospective multicenter database.